Mapping The Evolution of Good Governance: A Literature Review Perspective - Adila, Wafa (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
This study delineates the evolution of Good Governance through a literature review perspective, detailing the concepts and practices of effective governance over time. Engaging in the analysis of recent literature, the research explores the initial definitions and dimensions of Good Governance, tracing significant changes and developmental peaks on a global scale. The evolution trends are systematically mapped through a thorough literature review, providing a comprehensive overview of how the concept of Good Governance has progressed. Key influencing factors, including the roles of globalization, technology, social and cultural changes, are identified and analyzed. The findings offer in-depth insights into the complexity and dynamics of Good Governance, with significant implications for future research, policy-making, and practices. This research not only serves as a primary reference for scholars but also provides valuable guidance for practitioners and policymakers interested in enhancing governance across diverse contexts. Keywords: Good Governance, Evolution, Literature